La caracterización del feminicidio de la pareja o expareja y los delitos de odio discriminatorio - Pérez Manzano, Mercedes (Pontificia Universidad Católica del Perú. Fondo Editorial, 2018)
This article aims to specify a coherent and useful interpretation of feminicide behavior (or as preferred by the author “femicide”), which is included, in a non -uniform manner- in several criminal definitions in Latin American legislations. Indeed, the author asserts the need for an individualized criminal protection of women against gender violence, and confirms the praiseworthy work it is being done in Latin America, yet femicide as a criminal offense in the region is not defined accurately. Thus, the author concludes this is the reflection of a criminal policy that suffers from inaccuracies, duplicities and, in some cases, excessive punitiveness. The author questions the criminal definition of femicide as the death of a “woman because of her condition as such” or other similar definitions that include the murder of a woman because of the mere fact of being a woman. When referring to the death of a woman committed by her partner or former partner, the author characterizes feminicide as a form of violence which constitutes an instrument of discriminatory domination, in other words, violence against women with the purpose of maintaining or re-establishing unequal power relationships or simply to reaffirm the discriminatory sense of his act, denying the victim his right to equality. From this perspective, the author discusses considering partner or former partner femicide as a hate crime, since the characteristic of this criminal definition is its collective dimension (the implicit threat to the collective) and the parallel fungible condition of the victim. In the opinion of the author, in partner or former-partner femicide the woman’s death is related to both the bias that exists towards women, how they should behaved (machismo), and what was expected of the victim (as herself). It is an individual phenomenon, of only one dimension. Under all these considerations the text culminates analyzing the Peruvian criminal type of femicide, acknowledging some successes but also reiterating their mistakes.

El texto pretende ofrecer una interpretación coherente y útil de la conducta feminicida (o femicida, en la expresión preferida por la autora) contenida principalmente, de manera no uniforme, en diversos tipos penales de las legislaciones latinoamericanas. Efectivamente, luego de afirmar la necesidad de una individualización en la protección penal de la mujer frente a la violencia de género y de constatar lo loables que resultan los enunciados penales latinoamericanos (pese a su carácter disperso), concluye que estos no son el reflejo de una buena política criminal. En efecto, sus enunciados adolecen de imprecisiones, duplicidades y, en algunos casos, de exceso de punitivismo. Para tal efecto, la autora cuestiona la definición del feminicidio como la muerte de «una mujer por su condición de tal» u otras expresiones semejantes —es decir, la muerte por el simple hecho de ser mujer—. Refiriéndose en concreto a la muerte de una mujer a manos de su pareja o expareja, la autora caracteriza el feminicidio como una forma de violencia constitutiva de ser instrumento de dominación discriminatoria, es decir, violencia que se ejerce contra la mujer para mantener o restablecer las desiguales relaciones de poder o, simplemente, para reafirmar el sentido discriminatorio de su acto, negándole a la víctima su derecho a la igualdad. Desde esta perspectiva, la autora discute la consideración del feminicidio de la pareja o expareja como delito de odio, pues lo característico de este es su dimensión colectiva (el significado de amenaza implícita al colectivo) y la paralela condición fungible de la víctima. En opinión de la autora, en el feminicidio de la pareja o expareja la muerte de la mujer se relaciona con el comportamiento concreto asignado prejuiciosamente (machismo) y esperado de la mujer concreta. Es un fenómeno de una dimensión, fundamentalmente, individual. Bajo todas estas consideraciones, el texto culmina analizando el tipo penal peruano de feminicidio, reconociéndole algunos aciertos, pero también reiterando sus desaciertos.
Partner or Former Partner Femicide’s Characterization and Discriminatory Hate Crimes
Keywords: Feminicidio; Femicidio; Delitos de odio; Violencia de género; Discriminación; Violencia instrumental; https://purl.org/pe-repo/ocde/ford#5.05.00